Correlation of Serum Parathyroid Hormone and Calcium Level among Pre- and Post-menopausal Women (Journal of Current and Advance Medical Research, 2022)
Background: Postmenopausal women are prone to osteoporosis due to estrogen deficiency.Objective: The purpose of the present study was to assess the correlation between serum parathyroid hormone level and serum calcium level among pre- and post-menopausal women.Methodology: This cross-sectional study was conducted in the Department of Physiology at Dhaka Medical College, Dhaka, Bangladesh during the period of January 2012 to December 2012. Women were selected from different areas of Dhaka city. Among them, postmenopausal women with age ranging from 50 to 60 years were taken as group A and apparently healthy premenopausal women with age ranging from 20 to 30 years were included as group B for comparison. Serum calcium and parathyroid hormone levels were estimated to assess the hormonal status in both groups.Results: A total number of seventy (70) postmenopausal women with age ranging from 50 to 60 years and duration of menopause was more than one year. Thirty (30) apparently healthy premenopausal women with age ranging from 20 to 30 years with regular menstrual cycle. Correlation between parathyroid hormone with serum calcium was analyzed. In group A, serum parathyroid hormone showed negative correlation with serum Calcium (r= -0.161, p= 0.184) which was statistically non-significant relationship. In group B, serum parathyroid showed positive correlation with serum calcium (r=+0.232, p=0.218) which was statistically non-significant relationship.Conclusion: In conclusion serum calcium is lower and serum parathyroid hormone is higher in postmenopausal women.Journal of Current and Advance Medical Research, January 2022;9(1):16-20